The urban landscape of Bakchias : a town of the Fayyum from the Ptolemaic-Roman Period to late antiquity - Buzi, Paola (Archaeopress Roman archaeology, 2020)
The Urban Landscape of Bakchias: A Town of the Fayyum from the Ptolemaic-Roman Period to Late Antiquity summarises the results of field research conducted on the archaeological site of Bakchias, located in the north-eastern part of the Fayyum region. Historical, historico-religious and papyrological studies are also presented. The book provides a clear and comprehensive overview of the rise and fall of the kome of Bakchias. The settlement was a thriving centre from at least the 26th dynasty up until the ninth or tenth centuries CE, although with differing levels of economic prosperity and urban development. Equal weight is given not only to the archaeological and topographical aspects but also to the historical and the religious, whilst never forgetting the relationship between the urban settlement and other villages of the Arsinoite nomos